2022
DOI: 10.3389/fpain.2022.845513
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experiences of Co-morbid Pain and Depression in Older African American Women and Their Preferred Management Strategies

Abstract: The intersection of race, gender, and age places older African American women at an increased risk for untreated physical pain and depression that can significantly diminish their quality of life. The objectives of this study were to (1) explore older African American women's perceptions of pain and depressive symptoms and how these symptoms influence each other, and (2) explore effective pain and depression alleviation strategies used by the women. We conducted five focus groups with older African American wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Within these focus groups, we explained GBGB and asked participants questions about their experiences with various pain management strategies, their perceptions of the GBGB intervention and their thoughts about adaptations (eg, number of visits, interventionists, etc.) ( 10 ). Themes from the focus groups were used to guide us in adapting the GBGB intervention.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within these focus groups, we explained GBGB and asked participants questions about their experiences with various pain management strategies, their perceptions of the GBGB intervention and their thoughts about adaptations (eg, number of visits, interventionists, etc.) ( 10 ). Themes from the focus groups were used to guide us in adapting the GBGB intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have explored this phenomenon in older African American women, highlighting a lack of research on this unique perspective ( 7 ). Drazich and colleagues found that older African American women experiencing comorbid pain and depressive symptoms described a link between their pain and depressive symptoms, and how it interfered with their daily lives and their interactions with healthcare providers ( 10 ). Various factors contribute to the inequities in pain and mental health outcomes in middle-aged and older African American women that present complexity in treating both conditions.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 3 more Smart Citations